A study on Relative Clause in English, Indonesian and Arabic Language: A Comparative Analysis - Dharmawati Dharmawati; Mulyadi Mulyadi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The research is conducted to an analysis on relative clause in three languages. The aim of this paper is to compare of relative clause in three languages, namely Indonesian, English and Arabic. The research stage in analyzing the data was data collection, data classifying, data presenting. The result of the research is similarities and differences in the structure of relative clause in English, Indonesian and Arabic. Types of relative clause in English are defining and non-defining clauses, types of relative clause in Indonesian are Restrictive and Non-Restrictive relative clause and types of relative clause in Arabic are definite and indefinite relative clause.